(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
In many countries,Corporate Governance is adopted as a means for ensuring shareholders interest are protected. Corporate Governance Code is a blue print to achieve the objective of corporate governance.The Nigeria Corporate governance code emphasized the implementation of gender board diversity among firms. However, the World Economic Forum report on Global Gender Gap in 2024 showed that Nigeria is 125th out of 140 countries on the Global Gender Gap Index. This index showed that Nigeria is still way behind other countries in terms of gender equality and inclusion. Hence, it is essential to evaluate the implementation of the Nigerian corporate governance code in order to determine the extent of its implementation around board gender diversity. The study adopted comparative survey design. The population involved twenty-six listed firms in Nigeria. Five listed banks and five list food and beverage firms were selected using Purposive sampling technique. Data were collected from their annual financial reports (2021-2024) and data were analysed using frequency, percentage and graphs. Results showed that the Nigerian Corporate Governance Code promoted gender board diversity more in the banking industry when compared to the food and beverage industries due to the mandatory CBN 30% threshold. It means that 2022 Corporate Governance policy by the Central Bank of Nigeria (CBN) promoted gender board diversity better in the finance industry than Nigerian Corporate Governance code 2018 by security and exchange commission (SEC) in the food and beverage industry. Comparing firms in both sectors, the companies in banking sector were better than their counterpart in food and beverage industries in term of the trend of compliance among the firms. Drawing from the conclusion, regulatory agencies like Security and exchange commission (SEC) should introduce a regulatory threshold in the Nigerian Corporate Governance code 2018 in order to promote board gender diversity in the food and beverage industry.